Contemporary approaches to religious vocations in Australia - Dixon, Robert E. (The Australasian Catholic record, 2021)
The low numbers of people entering religious life is a major contemporary challenge facing the Catholic Church in Australia. In May 2014, in response to this challenge, Catholic Vocations Ministry Australia (CVMA) invited the Pastoral Research Office of the Australian Catholic Bishops Conference to carry out a research study of recent vocations to religious life in Australia.